El decir veraz y la práctica pedagógica universitaria de cara al ejercicio de la libertad - Escobar Galo, Juan Pablo (2024)
This essay intends to think about the professional education offered by the university in its search for truth as an experience related to reality and the exercise of freedom. It thus analyzes pedagogical discourse in superior education. It also describes how actions can be taken to foster a coherent professional instruction that seeks to transform local and global reality. The essay concludes that, in order to attain an emancipating, critical professional education, it is crucial to modify traditional pedagogical discourse, to educate in parresia (truthful discourse), and to develop alternative educational models, all of which implies significant changes in university institutions, so that these become able to modify learning and teaching processes in the classroom.